2013
DOI: 10.4269/ajtmh.13-0219
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation among Culex pipiens Complex (Diptera: Culicidae) Populations from the Sacramento Valley, California: Horizontal and Vertical Transmission of West Nile Virus, Diapause Potential, Autogeny, and Host Selection

Abstract: The vector competence and bionomics of Culex pipiens form pipiens L. and Cx. pipiens f. molestus Forskäl were evaluated for populations from the Sacramento Valley. Both f. pipiens and f. molestus females became infected, produced disseminated infections, and were able to transmit West Nile virus. Form molestus females also transmitted West Nile virus vertically to egg rafts and F1 progeny, whereas f. pipiens females only transmitted to egg rafts. Culex pipiens complex from urban Sacramento blood-fed on seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 78 publications
(111 reference statements)
1
23
0
Order By: Relevance
“…However, the results for one virus may not apply to another virus. For example, populations of form pipiens and form molestus have been shown to have nearly identical susceptibility to WNV (Nelms et al 2013). Similarly, while populations of Cx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results for one virus may not apply to another virus. For example, populations of form pipiens and form molestus have been shown to have nearly identical susceptibility to WNV (Nelms et al 2013). Similarly, while populations of Cx.…”
Section: Discussionmentioning
confidence: 99%
“…pipiens and Cx. quinquefasciatus (Say) are similar in their response to WNV (Turell 2012, Nelms et al 2013, there are significant differences in their response to RVFV (Turell et al 2010, Turell 2012). In addition, Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vector competence of North American lines of biotype pipiens (Pennsylvania) and of biotype molestus (New Jersey) populations were equal, but lower than vector competence of their hybrid progeny (Ciota et al 2013a). In contrast, significant differences in vector competence were found between biotype pipiens (Woodland) and biotype molestus (Sacramento) populations (Nelms et al 2013). No differences in transmission rates were found between four different autogenous and anautogenous Cx.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies showed that proper identification and separation of biotypes is essential, because genetic differences between biotypes and populations influence vector competence (Brustolin et al 2016, Ciota et al 2013a, Nelms et al 2013). Furthermore, our previous studies showed that temperature is an important determinant of vector competence of Cx.…”
Section: Introductionmentioning
confidence: 99%